ANXIOLYTIC EFFECT OF MORIN IN MICE: Pharmaceutical Science-Pharmacology - MANGAIARKKARASI A; VISWANATHAN S; RAMASWAMY S; THARANI CB (International Journal of Life Science and Pharma Research, 2012)
The usage of benzodiazepines, the major class of anxiolytic drugs is invariably accompanied by many side effects like sedation and myorelaxation leading to incoordination of movements. Search for novel anxiolytic agents have identified flavonoids as potential compounds devoid of these adverse effects. In the present study, morin, a pentahydroxy flavone has been investigated in detail for its anxiolytic and other effects on central nervous system in mice. Morin employed in doses of 10, 25 and 50 mg/kg(s.c) was screened for its effect on anxiety using two well validated methods namely elevated plus maze and stair case test. It’s influence on other parameters of central nervous system functions was studied by using rotarod, openfield apparatus and pentobarbitone induced sleeping time. Morin displayed a dose-dependent anxiolytic effect similar to diazepam in the animal models of anxiety as revealed by a significant increase in the time spent in open arms of the elevated plus maze and significant reduction in the number of rearing responses in staircase test. In the openfield test morin treatment did not significantly change the number of squares crossed by mice compared to vehicle treatment. Similarly the balancing time of mice when placed on a rotarod was also not altered by morin treatment. These observations indicated that, morin neither altered the motor activity nor produced any myorelaxation in mice. Further, morin pretreatment did not significantly influence the sleeping time of mice after pentobarbitone administration.Taken together, the results of the present study have identified the novel anxiolytic effect of morin without producing sedation, myorelaxation or alteration of motor activity